Age and sex of Miagao Public Market vendors as determining factors in role preferences on women as portrayed in comic books - Alvarez, Lee
This research is about age and sex as determining factors in role preferences of the respondents on women as portrayed in comic books. , The researchers have chosen the market vendors of Miagao as respondents in this particular study for the reason that most market vendors, if not all, do read comic books. The researchers were able to gather a total of seventy (70) respondents. Of the seventy (70) respondents, thirty-two (32) or forty-six percent (46) are males and thirty-eight (38) or fifty-four percent (54) are females. In this study, it was found out that most of the respondents read comic books with the love theme and only a few read comic books having mixed themes. The researchers have also discovered that both the male and female respondents agree that women in most cases were presented in a more conservative rather than in the liberal light. Chi-square statistical tool with .05 level of significance was used and it resulted to the finding that there is no significant relationship between the age, the sex and the preference of the respondents with regards to the roles of women as portrayed in our local comic books.